Singlemode-multimode-singlemode fiber structure as compressive strain sensor on a reinforced concrete beam - Chew, S.P.; Zulkifli, Ahmad Zarif; Hamad, H.; Harun, Sulaiman Wadi; Lee, L.Y.; Razak, H.A.; Adikan, Faisal Rafiq Mahamd (Elsevier, 2018)
In this paper, we demonstrate a single-mode–multimode–single-mode (SMS) fiber structure to measure compressive strain in the elastic regime of a reinforced concrete beam. The fabrication method used to produce a 3.12 m reinforced concrete beam that met the Euro code (EC2) requirements was also demonstrated in this work. Strain measurement via the SMS sensor was calibrated using an electrical resistance strain gauge and a data logger to obtain accurate measurements of the strain. A linear transmission spectral red shift was observed as the strain value was increased from 0 mm/mm to 0.000116 mm/mm. Hence, the SMS sensor could provide a sensitivity of 3778.1 nm/(mm/mm) with a linearity of 0.9661.